2009
DOI: 10.1161/circulationaha.108.791723
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations in Nitric Oxide Synthase 1 Adaptor Protein Are Associated With Sudden Cardiac Death in US White Community-Based Populations

Abstract: Background-The ECG QT interval is associated with risk of sudden cardiac death (SCD). A previous genome-wideassociation study demonstrated that allelic variants (rs10494366 and rs4657139) in the nitric oxide synthase 1 adaptor protein (NOS1AP), which encodes a carboxy-terminal PDZ ligand of neuronal nitric oxide synthase, are associated with the QT interval in white adults. The present analysis was conducted to validate the association between NOS1AP variants and the QT interval and to examine the association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
139
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(146 citation statements)
references
References 37 publications
3
139
1
3
Order By: Relevance
“…In the general population, multiple SNPs have been identified that associate with an increased risk of cardiac arrest. [6][7][8] As such, it is possible that these same SNPs occur with increased frequency or have a magnified effect size in patients on dialysis as an explanation for the increased rate of cardiac arrest reported in the dialysis population. Alternatively, novel SNPs specific to patients with ESRD may explain the excess cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the general population, multiple SNPs have been identified that associate with an increased risk of cardiac arrest. [6][7][8] As such, it is possible that these same SNPs occur with increased frequency or have a magnified effect size in patients on dialysis as an explanation for the increased rate of cardiac arrest reported in the dialysis population. Alternatively, novel SNPs specific to patients with ESRD may explain the excess cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%
“…4 The discovery of predictive markers for cardiac arrest in ESRD could alter the practice of nephrology, because the risk of cardiac arrest is 5% per year in the dialysis population. 2,5 In the general population, genome-wide association studies have identified genetic polymorphisms that significantly increase the risk of cardiac arrest [6][7][8] ; however, their clinical application has been limited, because the rate of cardiac arrest is only 0.24% per year. 9 As such, a doubling of risk in the general population would still be too low to warrant empirical primary prevention therapy.…”
mentioning
confidence: 99%
“…Noteworthy, NOS1AP SNPs reached higher significance compared with SNPs in genes known to be causes of LQTS and SQTS (306,343). Furthermore, NOS1AP has been linked to sudden cardiac death (205,326).…”
Section: Posttranslational Regulation Of Potassium Channels In Proteimentioning
confidence: 99%
“…A number of genetic variants have been linked to rare, heritable arrhythmias and SCD not associated with coronary disease, 46,47 and some (eg, ion channel variants associated with QT duration) were viewed as candidates of interest for familial patterns of SCD in coronary heart disease. Although these candidates have not January 28, 2014 yet emerged as targets for risk prediction in SCD attributable to coronary heart disease, other common gene variants have been linked to SCD 48,49 or to surrogate, mainly electrocardiographic risk factors, in apparently healthy populations. [50][51][52] Alternative pathways that appear to modulate QT duration are among these, as are associations that do not necessarily involve QT control.…”
Section: Genetics Genomics and Proteomicsmentioning
confidence: 99%